VISUALISASI DATA LOKASI RAWAN BENCANA DI JAWA TENGAH MENGGUNAKAN POWER BI - Adesyahputra, Muh Kevin; Febrianto, Ricky; Khilmi Wibowo, Muhammad Nanang; Handayani, Titis (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2024)
The Central Java Province, as a disaster-prone region, faces risks due to both natural and human factors. Low awareness of disaster risks and insufficient mitigation efforts worsen the situation. This research utilizes Power BI to visualize disaster data, contributing to the understanding of risks. A quantitative method is employed with a focus on data analysis, collected from the Indonesian Disaster Risk Index. The data blending and cleaning phase ensure dataset quality and relevance before implementation into Power BI. An interactive dashboard is created with graphics such as tables, bar charts, and donut charts. Evaluation and analysis of the results are conducted to ensure the effectiveness of the visualizations. The findings indicate that forest fires are the most dominant disaster, followed by floods and landslides. Volcanic eruptions have the lowest frequency. Recommendations include enhancing preparedness for forest fires, in-depth analysis of disaster causative factors, periodic data updates, and improved collaboration among stakeholders.